A conceptual framework of antecedents and impacts of knowledge quality on SMEs’ competitiveness - Norshidah, Mohamed (World Scientific and Engineering Academy and Society, 2013)
Knowledge quality is a new concept. It refers to the extent to which individuals’ awareness and understanding towards ideas, logics, relationships, and circumstances are fit for use, relevant and valuable to context, and easy to adapt. The paper proposes that knowledge quality constitutes intrinsic knowledge quality, contextual knowledge quality, actionable knowledge quality, and accessibility knowledge. Knowledge quality requires an organization’s absorptive capacity, functional diversity, openness, lean organizational structure, friendly organizational culture, and technology utilization capabilities. The impacts of knowledge quality are improvisational and compositional creativity, which are enablers of innovation. This as a whole makes up competitiveness. This paper conceptualizes a model of competitiveness for small and medium-sized enterprises (SMEs) and develops 13 propositions based on the theories of sense making, knowledge management, and creativity.